2014
DOI: 10.4236/ojpm.2014.41005
|View full text |Cite
|
Sign up to set email alerts
|

An intervention to reduce psychosocial and biological indicators of stress in African American lupus patients: The balancing lupus experiences with stress strategies study

Abstract: Objective Very little is known about the impact of psychosocial stress on African American lupus patients. Due to the exposure of African Americans to a unique trajectory of stressors throughout life, it may be critical to understand the relationship between psychosocial stress and underlying biological mechanisms that influence disease activity and pathology in this high risk group. Methods The Balancing Lupus Experiences with Stress Strategies (BLESS) study piloted the validated “Better Choices, Better Hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
42
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

4
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 43 publications
1
42
0
Order By: Relevance
“…83–87 The follow-up reported varied from 6 weeks to 6 months. The Chronic Disease Self-Management Program (CDSMP) was the mode of self-management education/ implementation reported by each study; however, some studies also used electronic administrative records and disease activity data from medical histories, physical examination, phlebotomy and urine collection to assess changes 84…”
Section: Resultsmentioning
confidence: 99%
“…83–87 The follow-up reported varied from 6 weeks to 6 months. The Chronic Disease Self-Management Program (CDSMP) was the mode of self-management education/ implementation reported by each study; however, some studies also used electronic administrative records and disease activity data from medical histories, physical examination, phlebotomy and urine collection to assess changes 84…”
Section: Resultsmentioning
confidence: 99%
“…11,101–114 Evidence-based self-management interventions designed to enhance social support and provide health education, among patients with lupus, have reduced pain, improved function and delayed disability. 11,101,103115 Although there is no generally accepted self-management program available for SLE, 58 2 programs that have been shown to be successful in improving conditions in patients with arthritis are the Arthritis Self-Management Program and the generic Chronic Disease Self-Management Program. Each program incorporates 6 weeks of peer-led sessions ranging in disease-specific and more general self-help content.…”
Section: Introductionmentioning
confidence: 99%
“…Arthritis self-management education delivered by small-group, home study, computer, or internet modalities have demonstrated significant improvements in health distress, self-reported global health, and activity limitation, with trends toward improvement in self-efficacy and mental stress management [20,[36][37][38][39][40][41][42][43][44][45]. However, African Americans and women are still disproportionately impacted by lupus [46][47][48][49][50][51][52].…”
Section: Discussionmentioning
confidence: 99%